MAT 382 - Introductory Numerical Methods January 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of FOUR (4) pages (including front page) of material before you begin the examination. Please refer to the examination guide that was uploaded in the E-Learning Portal. Instructions : Answer ALL questions.